2017
DOI: 10.1108/mip-04-2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging medium-sized sport events to attract club participants

Abstract: PARTICIPANTS AbstractPurpose -Sport participation is the lifeblood of community sport clubs. This research investigates how sport clubs can leverage participation from local, medium-sized, elite sport events. Design/methodology/approach -This study used an action research approach where researchers, along with representative stakeholders from two elite tennis tournaments and 23 local tennis organizations, collaborated to develop and implement a series of interventions as part of a wider leveraging plan. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Small and medium spectator events show mixed results as to whether or not the event had stimulated sport participation, as two studies concluded that the event under investigation had positively impacted sport participation (i.e., Ramchandani and Coleman, 2012 ; Ramchandani et al, 2015 ), while three studies concluded that the event had no impact on sport participation (i.e., Taks et al, 2014 ; Hodgetts and Duncan, 2015 ; Misener et al, 2015b ). Interestingly, six of the studies found mixed results in that there was not enough evidence to support a claim of increased participation or there was increased participation among certain populations and no changes in participation among others (i.e., Taks et al, 2013 , 2015 , 2018 ; Derom and VanWynsberghe, 2015 ; Misener, 2015 ; Hoskyn et al, 2018 ). There is an additional gap with regard to the role of smaller sport events in contributing to sport participation outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small and medium spectator events show mixed results as to whether or not the event had stimulated sport participation, as two studies concluded that the event under investigation had positively impacted sport participation (i.e., Ramchandani and Coleman, 2012 ; Ramchandani et al, 2015 ), while three studies concluded that the event had no impact on sport participation (i.e., Taks et al, 2014 ; Hodgetts and Duncan, 2015 ; Misener et al, 2015b ). Interestingly, six of the studies found mixed results in that there was not enough evidence to support a claim of increased participation or there was increased participation among certain populations and no changes in participation among others (i.e., Taks et al, 2013 , 2015 , 2018 ; Derom and VanWynsberghe, 2015 ; Misener, 2015 ; Hoskyn et al, 2018 ). There is an additional gap with regard to the role of smaller sport events in contributing to sport participation outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of event leveraging studies looking into how to effectively leverage non-mega sport events for sport participation impacts show mixed results (Misener et al, 2015a ; Chalip et al, 2017 ; Hoskyn et al, 2018 ; Taks et al, 2018 ). Effective leveraging strategies have yet to be identified, with results largely indicating that sport clubs lack the capacity to engage in leveraging strategies (Taks et al, 2018 ) or event attendees engage minimally with leveraging initiatives (Hoskyn et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the second implication for marketers, given the growing interest in CE practices (MSI, 2018) and sports marketing (Hoskyn et al , 2018), managers could use this study to refine their social media strategies in order to have their content more spreadable and likeable. Furthermore, the use of the adapted VBCEP typology and content category grid as proposed in this research can help managers to stimulate the co-creation of meaning for brands on Twitter, since the VBCEP (Hollebeek et al , 2017) typology originally comes from members interaction and their consumption experiences.…”
Section: Discussionmentioning
confidence: 99%
“…As the cities had limited temporal, financial, and human resources, their priorities emphasised delivery of daily operations. Previous research has identified insufficient resources as a constraint to leverage (Bell & Gallimore, 2015;Clark & Misener, 2015;Hoskyn et al, 2018), as well as prioritising daily operations (Chalip et al, 2017;Kennelly et al, 2017).…”
Section: )mentioning
confidence: 99%